Effectiveness of clove oil as anesthesia of Sergeant Major Abudefduf vaigiensis (Quoy & Gaimard, 1825) - Amris, Ainun Ayu Utami; Rahim, Sri Wahyuni; Yaqin, Khusnul (Sekolah Tinggi Ilmu Pertanian Wuna, 2020)
The increasing demand for live ornamental fish for export needs triggers fishermen to start looking for alternative fishing techniques that are more effective and efficient. The technique commonly used is the anesthetic technique using potassium cyanide. The use of cyanide has been banned by the government because of the many impacts it has caused such as the degradation of coral reef ecosystems, high non-target fish mortality and pollution of coastal areas. Clove oil is an alternative anesthetic which can be utilized with many advantages compared to cyanide. The sampled fish used was sergeant major (Abudefduf vaigiensis) as many as 15 fish with a size of 9-12 cm obtained from fishermen's catch using a scoop. The purpose of this study was to determine the optimal concentration of clove oil as an anesthetic of Sergeant Major Fish (Abudefduf vaigiensis) based on induction time Â and recovery time. The experimental design used was a Completely Randomized Design (CRD). Analysis of the data used is One-Way ANOVA parametric analysis and Kruskal Wallis nonparametric analysis. The results obtained are five series of concentrations (20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm) which have a significant effect on induction time (20 ppm and 60 ppm) of sergeant major fish (Abudefduf vaigiensis) (P<0.05) The treatment of five concentration series (20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm) did not have a significant effect on the recovery time of the Sergeant Major Fish (Abudefduf vaigiensis) (P>0.05).